Anti-cancer activity of Myristica Fragrans: A review - DR. NIKHIL CHAUDHARI,; DR. NINAD SATHE, (International Journal of Pharma and Bio Sciences, 2018)
Jatiphala, commonly known as nutmeg (Myristica fragrans Houtt.) (Family: Myristicaceae), is a popular herbal plant in traditional Ayurvedic medicine, which has since long is being used as an antioxidant, anti-helminthic, bronchodilator, anti-tussive, expectorant, memory enhancer, anti-diabetic, anti-diarrhoeal, anti-depressant, hypolipidemic and hypocholesterolemic, aromatic, stimulant, narcotic, carminative, astringent, aphrodisiac, antithrombotic, anti-platelet aggregation, anti-fungal, anti-dysenteric, anti-inflammatory etc. This plant is pharmacologically and clinically evaluated for various activities like antioxidant, aphrodisiac, antimicrobial, hepato-protective, and anti-inflammatory. It is promulgated to possess a wide range of phytochemical constituents. The current review is presented to give a comprehensive account of all anti-cancer activities of nutmeg and active contains of its essential oil. It will be helpful to create interest towards nutmeg and may be useful in developing new and economical anti-cancer formulations with more therapeutic value. The part used of the selected plant is leaf, fruit, mace and seed without kernel. As per retrospective review dihydroguaiaretic acid-DHGA, eugenol, isoeugenol, ethyl-eugenol, methyl-isoeugenol, dehydrodieugenol, O,O'-dimethyl-dehydrodieugenol, 6,6'-dibromo-dehydrodieugenol, myristicin, terpinen-4-ol, dlimonene and ligans (mesodihydroguaiaretic acid, macelignan, fragransin A2 and nectandrin B) active principle and methanolic, ethanoic, acetone, benzene, chloroform, aqueous, freezed dried water extract, eugenol loaded Nano emulsions-NEs emulsified with modified starch are found having anti-cancer activity against 28 different cell lines of various origins and 3 animal models. Also, it can be used as chemopreventive ingredient in the herbal anti-cancer formulation. Totally 49 research articles, peer reviewed research papers, abstracts and classical texts were reviewed. Totally 44 references of anti-cancer activity of Jatiphala were noted during this research review.